RELEVANSI PERKULIAHAN FABRIKASI LOGAM DENGAN TUGAS MENGAJAR GURU DI SMK NEGERI SUMATERA BARAT - Suparno Suparno (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2016)
Based on observations in the field a lot of complaints from students practice field who feel less able to teach the theory and practice field Metal Fabrication . It can also be a briefing on the university of origin is not adequate . In addition to mastery of theory , it is also about teaching practice. In particular in the field of teaching practice is commonly seen Fabrication implementation has not been as expected , in terms of the materials used as well the implementation process of the lecture . For that reason a lot of the problems that cause lack relevant between what is given in the Department both in theory and in theory Fabrication given in class . This research is descriptive, which will describe the results of quantitative and qualitative research . Results of the assessment of each aspect of the course that respondents summed and calculated according to the percentage of votes aspect that has been made.